Uptake of Contraception Among Adolescent Girls and Young Women PrEP Clients: Leveraging the Opportunity to Strengthen HIV and Sexual and Reproductive Health Integration - Pleaner, Melanie; Fipaza, Zukiswa; Mabetha, Khuthala; Greener, Letitia; Ncube, Sydney; Butler, Vusile; Beksinska, Mags; Mullick, Saiqa (Frontiers in Reproductive Health, 2021)
The introduction of oral pre-exposure prophylaxis (PrEP) for HIV prevention was a major breakthrough in South Africa (SA). While the initial introduction focused on issues such as the development and implementation of new guidelines, supply, and the development of demand creation strategies, the need to integrate PrEP services with sexual and reproductive health (SRH) services has gained traction both globally and locally. Project PrEP was implemented in eight healthcare facilities and four mobile clinics in three provinces in SA. Using monitoring data from across the four project clusters, and 4,949 clients, over a 21-month period, we conducted an analysis of baseline routine monitoring data to examine contraceptive uptake in adolescent girls and young women (AGYW) initiating PrEP at project sites. Two-thirds of women (62.3%, n = 3,083) reported the current use of contraception at baseline, with the most commonly used methods being hormonal injectables (61.9%, n = 1,829) and male condoms (19.4%, n = 575). A third (32.3%, n = 603) of the non-contraceptive users accepted a method at PrEP initiation. From a total of 1,007 (32.7%) current contraceptive users at baseline, 865 (85.9%) chose the same or a different method at this visit. The method uptake at PrEP initiation increased the overall contraceptive prevalence by 12.2 to 74.5%. Data indicated that over a third (38.8%, n = 725) who were not using a method at baseline described themselves as consistent condom users. Although a major focus of the project was on PrEP service provision, all women were counseled and offered contraceptive services. The acceptance of a method by a third of non-users was promising; however, more understanding of those who did not take up a method is required. The need to leverage opportunities for the promotion of the integration of HIV and family planning at all levels of PrEP provision was highlighted.